KEPEMIMPINAN DAN PENDIDIKAN ISLAM - Habibur Rahman; Raima Selviana (Universitas Trunojoyo Madura, 2018)
ABSTRACTLeadership is a conscious effort carried out by someone (leader) to be able to realize the goals of the organization through other people by providing motivation so that other people want to implement it, and for that it requires a balance between the individual needs of the implementers. A leader must understand and understand the basics of leadership to be a leader, both in a small scope, such as family, discussion leaders, etc. as well as leaders in a large scope such as organizational leaders, religious leaders, country leaders and so on . But there are several factors for the emergence of leadership: first, the factors of situation and condition; second, the ability factor; third, heredity; fourth, the appointment factor; fifth, the factor of interest. Education is a process of guidance, educating that is given intentionally to students by adults to achieve the goals of education itself. Islamic education is the formation of personality to become a human being with moral character so that in everyday life to get happiness, peace, and can reflect the behavior according to Islamic shari'a which originates in the Qur'an, Sunnah Rasul and Ijtihad. Educational leadership is the ability to drive the implementation of education to achieve educational goals. This understanding is in line with the angle of leadership philosophy which basically upholds the principle of humanity.